2016
DOI: 10.1200/jgo.2015.002469
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Abnormalities in South African Women Living With HIV With High Screening and Referral Rates

Abstract: PurposeTo determine the prevalence of screening, cervical dysplasia, and malignancy on the basis of histologic diagnoses from colposcopy and large loop excision of the transformation zone among women living with HIV (WLWH) who attended an urban antiretroviral treatment (ART) clinic in KwaZulu-Natal, South Africa.Materials and MethodsWe performed a retrospective cohort study to examine a random sample of 462 WLWH during a 5-year period from 2004 to 2009. Women on ART for < 3 months were excluded. Data were abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…during their study, at a stage termed "progression visit" noticed that 35% had progressed to ASCUS, 0.37% to ASC-H, 57% to LGSIL, 7% to HGSIL and 0.41% to cancer. From our study, other categories, LSIL and HSIL were of lower prevalence compared to Dim et al, (2011) and reports from outside our study center on HIV+ve not on therapy, hence one can say that HAART reduces progression of cervical dysplasia among HIV+ve females, which is consistent with some previous reports (Minkoff et al, 2010;Alder et al, 2012;Firnhaber et al, 2012;Blitz et al, 2013;Ezechi et al, 2014;Katz et al, 2016). Firnhaber et al, (2012) concluded that HAART use reduced the rate of incidence and progression of cervical lesions among HIV+ve females and was dependent on duration of regimen but Menon et al, (2017), reported in their systematic review of effects of HAART on cervical dysplasia in sub Saharan Africa, suggested that CD4+ cell count may have a more instrumental role in cervical oncogenesis or the integration of the latent reservoir throughout the body than either HAART use or the treatment duration on the prevalence of CIN 2 and CIN 3.…”
Section: Discussionsupporting
confidence: 92%
“…during their study, at a stage termed "progression visit" noticed that 35% had progressed to ASCUS, 0.37% to ASC-H, 57% to LGSIL, 7% to HGSIL and 0.41% to cancer. From our study, other categories, LSIL and HSIL were of lower prevalence compared to Dim et al, (2011) and reports from outside our study center on HIV+ve not on therapy, hence one can say that HAART reduces progression of cervical dysplasia among HIV+ve females, which is consistent with some previous reports (Minkoff et al, 2010;Alder et al, 2012;Firnhaber et al, 2012;Blitz et al, 2013;Ezechi et al, 2014;Katz et al, 2016). Firnhaber et al, (2012) concluded that HAART use reduced the rate of incidence and progression of cervical lesions among HIV+ve females and was dependent on duration of regimen but Menon et al, (2017), reported in their systematic review of effects of HAART on cervical dysplasia in sub Saharan Africa, suggested that CD4+ cell count may have a more instrumental role in cervical oncogenesis or the integration of the latent reservoir throughout the body than either HAART use or the treatment duration on the prevalence of CIN 2 and CIN 3.…”
Section: Discussionsupporting
confidence: 92%
“…Delays in colposcopy vary considerably between settings, from an average of 39 days from referral to colposcopy in one study in KwaZulu Natal, South Africa,12 to around 5–6 months in both our study and another in the Western Cape 23. It is concerning that time from Pap smear to colposcopy is >6 months for half the women at CMJAH, and a third at HCHC.…”
Section: Discussionmentioning
confidence: 54%
“…A range of health systems and patient factors influence access to colposcopy. System barriers include a limited number of colposcopy services, which are mostly centralised within tertiary-level facilities, with long waiting times for patients and few opportunities for non-specialist health workers to develop requisite skills 12. There are limited numbers of specialist gynaecologists within the public sector, and the high demands on these doctors for emergency and curative obstetric and gynaecology services may reduce their time available for diagnostic or preventive interventions, such as colposcopy.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality rates were not reported by the NCR. Studies have estimated that of the approximately 80% of black African women who are diagnosed, 60% are latently diagnosed and die (Katz et al, 2016;Mqoqi, Kellett, Sitas, & Musa, 2004). However, there is currently no data available to support cases definitively.…”
Section: Health Care System In South Africamentioning
confidence: 99%
“…From "Human Papillomavirus and Related Diseases in South Africa: ICO Information Centre on HPV and Cancer", by Bruni et al, 2016, p.33 By contrast, breast cancer is the leading cancer for women of all ages in SA followed by cervical cancer and lung cancer (Bruni et al, 2016). Factors contributing to this high burden of cervical cancer include challenging socioeconomic conditions, competing health needs, disproportionate HIV rates, and health care infrastructure challenges (Denny, 2010;Finoacchario-Kessler et al, 2016;Katz et al, 2016;UNAIDS, 2015).…”
Section: Health Care System In South Africamentioning
confidence: 99%